2019
DOI: 10.1016/j.chom.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The Prevotella copri Complex Comprises Four Distinct Clades Underrepresented in Westernized Populations

Abstract: SummaryPrevotella copri is a common human gut microbe that has been both positively and negatively associated with host health. In a cross-continent meta-analysis exploiting >6,500 metagenomes, we obtained >1,000 genomes and explored the genetic and population structure of P. copri. P. copri encompasses four distinct clades (>10% inter-clade genetic divergence) that we propose constitute the P. copri complex, and all clades were confirmed by isolate sequencing. These clades are nearly ubiquitous and co-present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
395
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 326 publications
(461 citation statements)
references
References 147 publications
27
395
0
2
Order By: Relevance
“…The gut microbiome is influenced by several factors including diet [2], physical activity [3], use of antibiotics [4], and other lifestyle-related conditions. Studies comparing the microbiome of rural and industrialized communities have also shown that dietary and lifestyle changes linked to Westernization have played a pivotal role in the loss of many microbial taxa and in the rise of others [5][6][7][8][9][10][11][12][13][14]. Although it is difficult to establish causality and mechanisms for these links [15,16], recent studies have extended the identifiable members of the human microbiome to now cover > 90% of its overall diversity [11], which is a prerequisite for advancing the understanding of the role of microbes in human physiology and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome is influenced by several factors including diet [2], physical activity [3], use of antibiotics [4], and other lifestyle-related conditions. Studies comparing the microbiome of rural and industrialized communities have also shown that dietary and lifestyle changes linked to Westernization have played a pivotal role in the loss of many microbial taxa and in the rise of others [5][6][7][8][9][10][11][12][13][14]. Although it is difficult to establish causality and mechanisms for these links [15,16], recent studies have extended the identifiable members of the human microbiome to now cover > 90% of its overall diversity [11], which is a prerequisite for advancing the understanding of the role of microbes in human physiology and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…indicating high genomic diversity of the different species 140 as well as a high differentiation among 513 strains of the same species, as for instance P. copri 141 . It is well documented that bacteria can 514 modulate the lymphocyte differentiation by the SCFAs (as previously 142 ), whose composition can 515 vary (qualitatively and quantitatively) based on the inflammatory status, as we have recently shown 516 for different intestinal gastrointestinal pathologies, such as celiac disease, adenomatous polyposis and 517 CRC 143 .…”
Section: Statistical Analysis Of the Association Between Tissue Micromentioning
confidence: 99%
“…Then, to determine whether the paleofeces DNA exhibits appropriate molecular behavior for aDNA, such as DNA damage, the merged reads from each sample were mapped to the genome of Prevotella copri (DSM 18205), and mapDamage 2.0 (Jonsson, Ginolhac, Schubert, Johnson, & Orlando, 2013) was used to measure the frequency of nucleotide deaminations that are characteristic of aDNA. P. copri was selected because it has been reported in both human and dog gut microbiota (Li et al, 2017;Tett et al, 2019).…”
Section: Assessment Of Paleofeces Microbial Preservationmentioning
confidence: 99%